Lithuanian Exporters in the Financial Crisis - Jensen, Camilla; Rasteniene, Aušryte (Ekonomika, 2016)
Using Enterprise Survey data covering the period 2001–2011, the paper investigates the export behavior of Lithuanian firms and changes herein before, during and after the financial crisis. The primary objective is to investigate if there are changes in export behavior such as frequency, intensity, value and structure, hence focus lies on the results obtained with the standard enterprise survey data that is annual and collected before and after the crisis. The findings show that in a quantitative perspective the financial crisis has only a marginal impact on the long run exporting behavior of Lithuanian firms. There are no significant changes in number of exporters and exported percentage and only a small but negative effect on exported value when using simple ANOVA (F-test) analysis or more advanced regression analysis for repeated cross sections and panel data. The impact of the crisis falls more on the qualitative aspects of exporters from Lithuania. Generally do exporters, though affected by the crisis, outperform local market oriented firms in and over the crisis on factors such as productivity, sales growth and quality. Complementary evidence from the more ad-hoc and short-term focused financial crisis surveys corroborates the findings from the standard enterprise surveys. In every aspect investigated did exporters perform at least as well and often much better than firms catering solely to the local market. The financial crisis survey data reveals that exporters had higher capacity utilization, lower levels of indebtedness and recovered generally faster than other firms from the crisis. For the methodology, we conclude with this paper that the usage of repeated cross sections from the Standard enterprise surveys is the best way to investigate our research questions. This owes to the large drop in number of observations in the panel dataset published by the World Bank, making those results overtly vulnerable to outliers in the sample and unobservable attrition factors. The financial crisis survey data is mainuly useful towards understanding short run adjustments and financial aspects of the crisis, while structural aspects and exporting behavior is better covered with the standard surveys. The main methodology problem of using less than population data (making it sensitive to survey sampling routines) to investigate exporting behavior in general concerns the enormous skewedness that exists within the population of exporting firms. This owes to the phenomena that in most countries a handful of (multinational and locally owned) firms account for more than 50% of total exports. This is also increasingly true for a country such as Lithuania as the transition towards a market and open economy has progressed.